2016
DOI: 10.1021/acs.jpcc.6b01348
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Quantification Framework Applied to the Water–Gas Shift Reaction over Pt-Based Catalysts

Abstract: This paper presents a systematic approach to quantify uncertainties of various quantities of interest (QoIs) in catalysis determined by microkinetic models developed from first principles. One of the main sources of uncertainty in any microkinetic simulation is attributed to the exchange-correlation approximations in density functional theory (DFT) used to calculate the rate constants for all elementary reaction steps within transition state theory. These DFT approximations are at the core of significant discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
95
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(101 citation statements)
references
References 59 publications
(114 reference statements)
2
95
0
4
Order By: Relevance
“…[115][116][117][118] In this work we utilize the error estimation capabilities of the BEEF-vdW functional 75 in order to estimate its accuracy and quantify the uncertainty due to the GGA approximation. Although the quantitative accuracy of BEEF-vdW error estimation in oxide materials is not well-known, 119 the BEEF-vdW ensembles provide a systematic way to assess the sensitivity of conclusions to accuracy of approximations. 120 The error bars shown in this work correspond to ±1σ of the ensemble of 2000 energies provided by the BEEF-vdW functional.…”
Section: Computational Density Functional Theorymentioning
confidence: 99%
“…[115][116][117][118] In this work we utilize the error estimation capabilities of the BEEF-vdW functional 75 in order to estimate its accuracy and quantify the uncertainty due to the GGA approximation. Although the quantitative accuracy of BEEF-vdW error estimation in oxide materials is not well-known, 119 the BEEF-vdW ensembles provide a systematic way to assess the sensitivity of conclusions to accuracy of approximations. 120 The error bars shown in this work correspond to ±1σ of the ensemble of 2000 energies provided by the BEEF-vdW functional.…”
Section: Computational Density Functional Theorymentioning
confidence: 99%
“…Poor functional choice for a given reaction has yielded unphysical mechanistic predictions, such as barrierless hydrogen abstraction 81 , spurious complex-substrate charge transfer [81][82] or identification of the wrong reactive spin surface 83 . Uncertainty quantification [84][85][86] from statistical analysis of an ensemble of functionals can be used as a tool to introduce confidence intervals to catalytic predictions for a single catalyst or cycle if a suitable ensemble of functionals is chosen. Complementary to this approach, a broader understanding of prediction sensitivity to the most commonly varied functional parameters is needed in computational catalysis. Unlike spin-state splitting, relationships between catalytic intermediate structure and either exchange sensitivity or semi-local DFT errors are not yet well known.…”
Section: Introductionmentioning
confidence: 99%
“…The iron oxide‐based catalysts are prone to coke formation, and the commercial copper‐based catalysts deactivate in the presence of condensed water . Hence, to address these drawbacks, other metals, like noble metals, were investigated to substitute the commercial catalysts . Since the noble metals are expensive and usually deactivate in contact with sulphur, researchers investigated the activity of transition metals or metal oxides to catalyze WGSR …”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Hence, to address these drawbacks, other metals, like noble metals, were investigated to substitute the commercial catalysts. [3,[10][11][12][13][14][15][16][17][18] Since the noble metals are expensive and usually deactivate in contact with sulphur, researchers investigated the activity of transition metals or metal oxides to catalyze WGSR. [1,2,4,6,19,20] Further research on WGSR has revealed that cerium oxide has high oxygen storage capacity and promotes WGSR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation